Nutritional composition and "in vitro" digestibility of corn genotypes evaluated in two years - Tres, Tamara Tais; Jobim, Clóves Cabreira; Pinto, Ronald José Barth; Souza Neto, Israel Leite de; Scapim, Carlos Alberto; Silva, Mábio Silvan José da (Semina: Ciências Agrárias, 2014)
The objective of this study was to evaluate the chemical composition, quantitatively characterize, in a comparative way, the carbohydrate fractions of commercial corn hybrids and of materials from crossing between hybrids for silage production. Therefore, 14 multiple hybrids, 7 commercial hybrids, 7 selffertilized from commercial hybrids progenies and 2 controls were evaluated in two agricultural years. The 2B710 hybrid showed high dry matter in vitro digestibility in the first year and fiber fraction in the two years of evaluation. The progeny P30P34 x P30P34 showed high dry matter digestibility and fiber fraction in two years. The highest fraction of non-fibrous carbohydrates (A+B1) was found for the crosses IMPACTO x CD308 and P30R50 x CD308 for the first and second year respectively, indicating a greater efficiency in providing readily available energy in the rumen. The significant interactions between corn hybrids and agricultural years for chemical composition showed that the growing environment has great influence on the nutritional composition, leading to the necessity of evaluating multiple environments in order to select corn for silage production.